Support system for novice researchers (SSNR): usability evaluation of the first use - Ismail, M.; Yaacob, M.; Abdulkareem, S.; Nasaruddin, F.; Abdullah, N. (2012)
Scholars make use of research output in the form of conference proceedings, journal and theses as references as guideline in generating new knowledge for the use of future generations. Support in the early stage of study is crucial for novice researchers as it will give them some insights of where to seek for extra information on relevant literature, institutions, people and research trend without having to go through tedious process of identifying this information all by themselves. The result of the implementation of SSNR shows significant information that can be utilized by novice researchers in accelerating research process. Thus, this paper will discuss on the evaluation of SSNR by novice researchers, in terms of its usability. The results are promising which indicated that SSNR work as it should.